1940
DOI: 10.1037/h0054950
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning in the spinal dog.

Abstract: Positive evidence that the spinal cord, when completely severed from the brain centers with which it is normally associated, is capable of establishing a substitute or 'conditioned' response (CR) has not hitherto been reported. 8 Heretofore the higher brain levels, whether of cortex (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

1942
1942
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 8 publications
(5 reference statements)
2
37
0
Order By: Relevance
“…Early studies by Shurrager and his associates (e .g., Shurrager and Culler, 1940), which indicated that stimulus pairing produced alterations in spinal reflex responses, were not replicated by studies of Kellogg and his associates (e.g., Kellogg, Pronko, & Deese, 1946) who generally failed to find changes in spinal reflex responses with stimulus pairings or who thought such increases to be due to other factors. Subsequent studies (e.g., Buerger & Dawson, 1969;Uoyd, Wikler, & Whitehouse, 1969), utilizing numerous methodologies and preparations with both chronic and acute spinal animals, have found both positive and negative effects of stimulus pairings on spinal responses.…”
mentioning
confidence: 77%
“…Early studies by Shurrager and his associates (e .g., Shurrager and Culler, 1940), which indicated that stimulus pairing produced alterations in spinal reflex responses, were not replicated by studies of Kellogg and his associates (e.g., Kellogg, Pronko, & Deese, 1946) who generally failed to find changes in spinal reflex responses with stimulus pairings or who thought such increases to be due to other factors. Subsequent studies (e.g., Buerger & Dawson, 1969;Uoyd, Wikler, & Whitehouse, 1969), utilizing numerous methodologies and preparations with both chronic and acute spinal animals, have found both positive and negative effects of stimulus pairings on spinal responses.…”
mentioning
confidence: 77%
“…Culler was the first to examine whether spinal neurons can support Pavlovian conditioning (Culler, 1937; Shurrager & Culler, 1940). Using tailshock as a CS, and hindpaw shock as the US, evidence was obtained for both the acquisition and extinction of a conditioned response in spinally transected animals.…”
Section: Pavlovian Conditioningmentioning
confidence: 99%
“…The second controversial issue concerned claims that the CS had no capacity to generate a CR-like behavior prior to training (Shurrager & Culler, 1940). The implication was that training established a new ( de novo ) association.…”
Section: Pavlovian Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditioning of the flexion reflex in the acute spinal carnivore was first reported by Shurrager & Culler (1940). The ensuing controversy (see Kellogg et al, 1947) left the issue unresolved, particularly for the acute preparation.…”
mentioning
confidence: 99%